2007
DOI: 10.1177/154405910708600405
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Amelogenesis Imperfecta Inferred from Amelogenin Evolution

Abstract: We used the evolutionary analysis of amelogenin (AMEL) in 80 amniotes (52 mammalian and 28 reptilian sequences) to aid in the genetic diagnosis of X-linked amelogenesis imperfecta (AIH1). Out of 191 residues, 77 were found to be unchanged in mammals, and only 34 in amniotes. The latter are considered crucial residues for enamel formation, while the 43 residues conserved only in mammals could indicate that they play new, important roles for enamel formation in this lineage. The 5 substitutions leading to AIH1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…This also reveals that the protein needs to be highly structured on its full-length for a correct function of the enzyme. This high selective pressure along the whole sequence length contrasts with the low constraints observed in unstructured (disordered) proteins previously studied: AMELX (40% of sensitive positions (27)), ENAM (7% (28)), MEPE (14% (29)), AMTN (8% (30)), DMP1 (20% (31)), and AMBN (18%). 7 This corroborates the crucial importance of TNSALP in mammals and its involvement in various functional, but also structural, roles, not yet exhaustively identified.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This also reveals that the protein needs to be highly structured on its full-length for a correct function of the enzyme. This high selective pressure along the whole sequence length contrasts with the low constraints observed in unstructured (disordered) proteins previously studied: AMELX (40% of sensitive positions (27)), ENAM (7% (28)), MEPE (14% (29)), AMTN (8% (30)), DMP1 (20% (31)), and AMBN (18%). 7 This corroborates the crucial importance of TNSALP in mammals and its involvement in various functional, but also structural, roles, not yet exhaustively identified.…”
Section: Discussionmentioning
confidence: 59%
“…Recently, our group successfully used this approach for predicting sensitive positions in various proteins of the secretory calcium-binding phosphoprotein family (26), and showed that missense mutations lead to genetic diseases. This approach was demonstrated on the following proteins: amelogenin (27), enamelin (28), matrix extracellular phospho-glycoprotein (29), amelotin (30), dentin matrix protein 1 (31), and ameloblastin. 6 Here, we perform the evolutionary molecular analysis of mammalian TNSALP to (i) highlight the functional or structural importance of various positions and domains; (ii) predict sensitive positions that should be responsible for a genetic disorder when substituted; and (iii) validate our predictions by using missense mutations reported in humans.…”
mentioning
confidence: 99%
“…This review will focus on the effects of human amelogenin gene mutations, and on animal models generated to reproduce the human AI genotype and phenotype. Similarities between human and murine amelogenin genes are apparent at the levels of gene structure, DNA sequence and pattern of expression during development 19 .…”
Section: Gene Mutations Lead To Amelogenesis Imperfecta (Ai) In Humansmentioning
confidence: 99%
“…The abundant, highly conserved amelogenins are expressed from the X-chromosomal amelogenin gene in mice [Chapman et al, 1991;Delgado et al, 2007]. The primary RNA transcript can be alternatively spliced to form at least 15 mRNAs [Hu et al, 1997;Li et al, 1998Li et al, , 2006, which are translated into amelogenin proteins that vary in abundance.…”
Section: Introductionmentioning
confidence: 99%